Characterization of cellulose nanocrystal-gold nanoparticles/chitosan modified screen-printed carbon electrode and its application in the fabrication of electrochemical biosensor for tetracycline detection - Hasim, Nurul Shahirah; Yusof, Nor Azah; Mohd Zawawi, Ruzniza; Nordin, Noordiana (Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 2022)
Tetracycline is one of the antibiotics used therapeutically and as a growth promoter in animals. Tetracycline residues in food products of animal origin have raised concerns among consumers. Due to its adverse effects on human health, it is critical to develop a reliable analytical method for routine monitoring of tetracycline in foods. Biosensors are among the rapid analytical devices that are reliable because of their simple detection methodology, low cost, sensitivity and specificity. For an effective signal transformation of tetracycline residues, it is critical to completely attach the transducer to the biological component, so that a feasible biosensor can be constructed. In this study, the screen-printed carbon electrode (SPCE) was modified with cellulose nanocrystal–gold nanoparticles/chitosan composite (CNC–AuNPs/chitosan). The synthesized CNC–AuNPs composite was characterized using UV–Vis spectroscopy, X-ray diffraction, Fourier-transform infrared spectroscopy and high-resolution transmission electron microscopy. In addition, the electrochemical behavior of the modified SPCE was investigated by cyclic voltammetry, differential pulse voltammetry (DPV) and electrochemical impedance spectroscopy under optimized conditions. DPV showed a linear calibration within the range of 0.01 to 1000 µM concentration of tetracycline with the detection limit of 0.07 µM. The developed biosensor also resulted in different peak currents measured after storage for 14 days at room temperature (53.07%) and under 4°C (89.28%). Therefore, with acceptable sensitivity and selectivity, the fabricated biosensor can be suggested as a potential detection method for tetracycline residues.